Miller-Dieker syndrome with ring chromosome 17. Issue 6 (June 1991) - Sharief, N; Craze, J; Summers, D; Butler, L; Wood, C B
Abstract : A girl presented at 6 weeks of age with failure to thrive and arching of the back. She had various dysmorphic features, hepatosplenomegaly, and developmental delay. The electroencephalogram and cranial ultrasound were abnormal, and a computed tomogram showed lissencephaly and apparent agenesis of the corpus callosum. Because of frequent aspiration she became oxygen dependent. She later developed intractable convulsions and died at the age of 9 months.